Development of Jombang Local Cultural Diversity Educative Games Science Material for Class IV Studens of SDN Mojojejer 2 Jombang - Zakaria, Afif Fadhilah; Harsiwi, Nova Estu (Citra Dharma Cindekia, 2025)
The aims of this research and development, are: (1) To develop valid learning media of Educational Games on Local Cultural Diversity in Jombang based on expert validation. (2) To develop effective learning media of Educational Games on Local Cultural Diversity in Jombang based on learning implementation sheets (teacher and student activities) and student cognitive learning outcomes. (3) To develop interesting learning media of Educational Games on Local Cultural Diversity in Jombang based on student and teacher response questionnaires. This research is a research and development that refers to the ADDIE model (analyze, design, development, implementation, evaluation). Based on the results of the research that has been carried out, the percentage of validity of the Jombang Local Cultural Diversity Educational Game learning media is obtained in terms of the results of the media expert validator 90%, the language expert validator 93%, the material expert validator 97% with all three in the category